A development of the Philippine Tables for LC Class H - Rosali, Rosemarie G.; Angeles, Belen B.; Austria, Pacifico M. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1983)
This special problem is an expansion of the Library of Congress Class H for the Philippines based on the latest LC Class H schedules. It covers the Social Sciences (H) ; Statistics (HA) ; Economics (HB, HC , HD, HE, HF, HG, HJ) ; Sociology (HM) ; Social History and Conditions, Social Problems, Social Reform (HN) ; Family, Marriage, Woman (HQ) ; Associations, Societies, Clubs (HS) ; Communities, Classes, Races (HT) ; Social Pathology, Social and Public Welfare, Criminology (HV) ; and Socialism, Communism, Anarchism (HX).
Expansion in this sense required a development of the Philippine tables based on the standards numbers assigned by LC. The method used is compatible with the rest of the LC expansion schemes with regard to the use of form divisions, internal subdivisions, chronological tables (except in cases where period subdivisions have to be detailed based on the country's historical periods), subject division tables, and combination tables. Only topical areas or subjects requiring specific class numbers for the Philippines are included. Subject areas of general nature are excluded. In the development of the Philippine tables, the process of arriving at the numbers assigned to the Philippines is explicitly presented.
These tables attempt to help Filipiniana catalogers save time and seek to provide conformity and uniformity. The purpose is essentially to provide an LC-patterned scheme for the Philippines that can be consulted quickly and easily.
Mimeographed.
Keywords: Classification, Library of Congress; Classification -- Books -- Philippines; Classification -- Books -- Social Sciences